High-performance produced water treatment using cactus-inspired coalescing media with hierarchical PVDF/MnO2 nanoflakes/CNT composites - Oluwaseun Ogunbiyi (16931805) (2025)
Produced water from oil and gas fields represents the largest waste stream from these industries, characterized by high oil content, high salinity, and non-neutral pH values, posing significant environmental hazards. Coalescing separation is an environmentally friendly water treatment technology. Efficient oil separation from wastewater relies on advanced designs for the structure and wettability of coalescing materials. Inspired by the cactus's surface structure for liquid capture, this study introduces a novel coalescing medium with a hierarchical structure composed of polyvinylidene fluoride/manganese dioxide nanoflakes/carbon nanotubes composite. The carbon nanotubes form a three-dimensional, interconnected porous network, allowing free oil/water flux. The manganese dioxide nanoflakes, resembling cactus protrusions, on carbon nanotubes further create more active sites for oil particles’ agglomeration. The composite media's surface is modified with an ultrathin layer of hydrophobic polyvinylidene fluoride, providing resistance to salt and pH corrosion. This innovative coalescing medium achieved an emulsified oil/water separation efficiency of up to 99% and maintained consistent performance in environments with a broad salinity range (300 – 45,000 ppm) and wide pH range (4 – 10). Given its high efficiency and durability under extreme conditions, this innovative coalescing medium with hierarchical structures proves to be a practical approach for oily wastewater treatment in the industry. Other Information Published in: Journal of Environmental Chemical Engineering License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.jece.2025.118070